Environmental Embrace Project: history and perspectives of post Covid-19 pandemic (Research, Society and Development, 2020)
Environmental Education projects that aim at non-informal environments actions are essential to raising awareness among the general population. In this sense, in 2015, the extension project in allusion to the day of the tree, called “Environmental Embrace” was carried out in the municipality of Umuarama – PR and was registered in RankBrasil as the biggest woodland hug in the country. In the following years, the project gained strength and dynamism through Environmental Education workshops in different locations and always culminating in a group hug in the Uirapuru forest. In 2020, due to the pandemic caused by Covid-19, it was necessary to reframe the action, since physical presence was no longer possible. Thus, in September, a virtual version of the Environmental Embrace was organized, in which people were encouraged to post on social media, their photos, videos, parodies, poetry, texts and drawings of actions related to the environment and especially related to the tree day, using the hashtag #abracoambiental2020. However, the participation of the population was not so expressive and among the possible causes of low adherence, there is the failure in disclosure, resistance to actions promoted by public educational institutions, and the excess of virtual activities. However, the results signal an urgent need to promote awareness actions about the environment, in an increasingly innovative and assertive manner. Whether before, during or after the pandemic.